Elected Member - Charalambous, Andreas (My University, 2026)
Elected Member of the University’s Union of Academics. As of 2010 I was elected member of the University’s Union of Academic representing Lectures and Associate Professors to the central union’s council. Parts of my duties include the exploration and addressing of problems, concerns and desires expressed by the union’s members in collaboration with the University’s governing body.